Oral empagliflozin-loaded tri-layer core-sheath fibers fabricated using tri-axial electrospinning: Enhanced in vitro and in vivo antidiabetic performance - TATAR, ESRA; GÜNDÜZ, OĞUZHAN (My University, 2023)
Empagliflozin (EM) was successfully loaded in polycaprolactone/poly (L-lactic acid)/polymethyl methacrylate (PCL/PLA/PMMA) fibers. In the rat β-cell line (BRIN-BD11), the insulin expression ratio of pancreatic β-cells was stimulated at high and low glucose by culturing with tri-layer EM-loaded fiber (EMF) for 48 h. The expression ratios of glucokinase and GLUT-2 proteins increased after EMF treatment. According to the in vitro drug release test, 97% of all drug contained in fibers was released in a controlled manner for 24 h. The pharmacokinetic test revealed that the bioavailability was improved ∼4.8-fold with EMF treatment compared to EM-powder and blood glucose level was effectively controlled for 24 h with EMF. Oral administration of EMF exhibited a better sustainable anti-diabetic activity even in the half-dosage than EM-powder in streptozotocin/nicotinamide-induced T2DM rats. The levels of GLP-1, PPAR-γ, and insulin were increased while the levels of SGLT-2 and TNF-α were decreased with EMF treatment. Also, EMF recovered the histopathological changes in the liver, pancreas, and kidney in T2DM rats and protected pancreatic β-cells. Consequently, EMF is suggested as an unprecedented and promotive treatment approach for T2DM with a higher bioavailability and better antidiabetic effect compared to conventional dosage forms.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TROPİKAL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; TROPICAL MEDICINE; Farmasötik bilim; Yaşam Bilimleri; Pharmaceutical Science; Life Sciences; Core-sheath fiber; Empagliflozin; Insulin resistance; Tri-axial electrospinning; Type 2 diabetes mellitus